ASEAN PEOPLE-CENTERED REGIONALISM AND STRATEGY TO BUILD ITS PEOPLE'S IDENTITY THROUGH SOCIAL MEDIA DISCOURSE - Sugito, Sugito (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
ASEAN has a great interest in creating a regional identity as a consequence of the people-centered regionalism goal. Although this identity creation is vital, the awareness of ASEAN identity is still relatively weak in ASEAN countries, even among elites and long-standing member countries. As an organization, ASEAN has the power to shape identity and norms for its people. Therefore, this study aims to reveal ASEAN’s strategy in shaping its identity through Facebook. This research argues that social media, which has become an interactive, participatory, and democratic media, should be able to be utilized by ASEAN in building agreement on its identity among its users. Through a qualitative approach by utilizing data processing and analysis software of NVIVO 12 Plus, this study concluded that ASEAN was concerned more with creating shared values ​​than exploring the cultural heritage in its member countries. ASEAN also was serious about displaying prosperity, mutual respect, and unity in diversity values as its identity.